ЗАРУБЕЖНОЕ ИСЛАМСКОЕ ОБРАЗОВАНИЕ КАК ФАКТОР РАДИКАЛИЗАЦИИ ИСЛАМСКОГО СОЗНАНИЯ МУСУЛЬМАН РОССИИ (НА ПРИМЕРЕ РЕСПУБЛИКИ ДАГЕСТАН) - Abdulagatov, Zaid Magomedovic (History, Archeology and Ethnography of the Caucasus, 2019)
The problems of religious extremism and terrorism in the regions of Russia have their own internal and external factors. A large number of Russian politicians, secular scientists, and Islamic leaders consider foreign Islamic education to be one of the most significant external factors in the radicalization of Islamic consciousness in Russia. In Russian public consciousness there is an opposite point of view. The text sets a goal to identify the nature of the influence of foreign Islamic education on the religious consciousness of Russian Muslims in the context of Islamic faith traditions in the Republic of Dagestan (RD). In particular, the task is to find out how justified the conclusion that foreign Islamic education forms a radical Islamic consciousness among Russian Muslims. The research methodology is mainly based on a sociological survey among Dagestan Muslims who studied in foreign Islamic educational institutions, from individuals. In addition, historical information about the influence of foreign Islamic education on religious behavior in the pre-Soviet period of Russian history was used. In the article, the author showed that foreign education was a problem for the Russian state in the pre-Soviet period of its history: North Caucasian Muslims returned from abroad with thoughts "dangerous for Russian statehood." Based on the data of a sociological survey of Muslims of Dagestan who studied abroad in the XXI century, it was revealed that about a third of them returned to their homeland with a Salafi confessional consciousness. This is an extremeness of consciousness, which contradicts the Sufi Islamic tradition prevailing in the republic, and in the future is capable of protesting radically Salafi activity in the region. The author comes to the conclusion that in the current situation it is desirable to promote “trustworthy” foreign educational centers, to actively work to organize the sending of Russian Muslims to these centers, to conduct democratic, within the framework of the law, control of people traveling independently.